Gender and Sexuality: What do the Infant Education Teachers from Canoas/Brazil say? - Quaresma da Silva, Denise Regina; Fanfa Sarmento, Dirléia; Fossatti, Paulo (Education Policy Analysis Archives, 2012)
This article focuses the conceptions of gender and sexuality of the infant education teachers of the municipal schools net of the city of Canoas (Rio Grande do Sul, Brasil). We listed the contributions that set up our theoretical opinions. Afterwards we analyzed the focal group that was accomplished with 26 teachers, where we presented to the group images that deal about the theme and listened to their understandings. The results point out the necessity of including themes of gender and sexuality in the professional graduation formation and post graduation in the Pedagogy area.